Sex-Related Differences in the Associations Between Wishing to Die, Grip Strength, and Physical Activity: An Analysis in European Middle-Aged and Older Adults - De Moraes-Ferrari, G (Elsevier B.V., 2025)
Background: The desire to die among older adults has been reported in several European countries. This study aimed to investigate the associations between grip strength (GS) and the frequency of weekly moderate physical activity (MPA) with wish to die (WTD) in European middle-aged and older adults. Methods: A cross-sectional analysis was conducted with 39,377 participants (22,313 women) from 27 European countries, aged ≥50 years, responding to wave 8 of the SHARE project. GS was assessed for both hands by a dynamometer, WTD was obtained by asking: ‘In the last month, have you felt that you would rather be dead?’ from the 12-item EURO-D scale, and the weekly frequency of moderate physical activity (MPA) was self-reported. Results: Greater GS (per 1 unit) was associated with a 26 % to 55 % lower chances of WTD among men. Among women, a 1 kg increase in GS was associated with a 40 % to 70 % lower chance of WTD. MPA once a week or more than once a week (compared to MPA less than once a week) was associated with a 57 % and 58 % lower chance of WTD among men. Among women, MPA once a week or more than once a week (compared to MPA less than once a week) was associated with 44 % and 48 % lower odds of WTD. Conclusion: GS was inversely associated with WTD, particularly in women. Engaging in MPA once a week showed a greater association with less WTD for both sexes than MPA more than once a week, particularly in men. © 2025 The Authors